2017
DOI: 10.21077/ijf.2017.64.1.53263-04
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of reef fishes in trap fishery at Keelakarai, Gulf of Mannar, south-east coast of India

Abstract: The diversity of finfishes caught in traps at Keelakarai, Gulf of Mannar was assessed quantitatively and qualitatively for a period of six years from July 2006 to June 2012. Average landing during the period was 109 t per year with maximum of 137 t during 2008-09. Among the 98 species of reef fishes landed, Siganus canaliculatus dominated (28%), followed by Scarus ghobban (21%). During the first two years of the study, S. ghobban dominated over S. canaliculatus and later the trend reversed. Family-wise, maximu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 3 publications
2
8
0
Order By: Relevance
“…In this study, Leiognathus equulus contributed 7.97% (with 1.47% average similarity) to the total similarity of trawl bycatches of Chennai coast. Meanwhile, Varghese et al (2017) reported that Siganus caniculatus contributed a maximum of 23.82% similarities to total similarity of reef fishes between the 2006 and 2012 along the southeast coast of India. The 95% confidence funnel of average taxonomic distinctness index (∆+) and variation in taxonomic distinctness index (/\+) values, showed no significant deviation in bycatch fish diversity between the seasons.…”
Section: Simper Taxtest and Linktreementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, Leiognathus equulus contributed 7.97% (with 1.47% average similarity) to the total similarity of trawl bycatches of Chennai coast. Meanwhile, Varghese et al (2017) reported that Siganus caniculatus contributed a maximum of 23.82% similarities to total similarity of reef fishes between the 2006 and 2012 along the southeast coast of India. The 95% confidence funnel of average taxonomic distinctness index (∆+) and variation in taxonomic distinctness index (/\+) values, showed no significant deviation in bycatch fish diversity between the seasons.…”
Section: Simper Taxtest and Linktreementioning
confidence: 99%
“…The 95% confidence funnel of average taxonomic distinctness index (∆+) and variation in taxonomic distinctness index (/\+) values, showed no significant deviation in bycatch fish diversity between the seasons. Varghese et al (2017) stated that 95% probability contours showed significant deviation in reef fish diversity at Keelakarai, Gulf of Mannar between 2006 and 2012. In this study, the 95% probability contours of average taxonomic distinctness index (∆+) and variation in taxonomic distinctness index (/\+) values were well within the funnel showing no significant deviation.…”
Section: Simper Taxtest and Linktreementioning
confidence: 99%
“…Seasonal abundance of coral reef-associated shes has been studied in Keelakarai region (Murugan & Durgekar, 2008) along with the diversity, occurrence, economic aspects of snappers and job sh sheries in the Gulf of Mannar region (Murugan et al, 2014). Comparative performance of three types of traps and diversity of reef shes collected from the trap shery at Keelakarai, Gulf of Mannar was described (Kalaiarasan et al, 2014;2015 andVarghese et al, 2017). With this backdrop, the present work was carried out to understand the catch and value of shes collected through trap shing and in uence of COVID-19 lockdown on the sh market value.…”
Section: Introductionmentioning
confidence: 98%
“…This method targets the catch of coral reef-associated shes (Varghese et al, 2008;Murugan and Durgekar, 2008). Many people prefer the trap shery in this region due to less capital investment for construction of traps, easy to haul from small traditional craft (Kattumaram) and high income accrued from the trap shery (Varghese et al, 2017). The variety of shes from the trap shery includes Parrot sh, Groupers, Rabbit sh, Emperors, Snappers, Goat shes, Grunts, Thread n bream, Trevally sh, trigger sh, Puffer sh and Porcupine sh.…”
Section: Introductionmentioning
confidence: 99%
“…It is a relatively small yet important fishery in the range countries (Heemstra & Randall, 1993;Kandula et al, 2015;Russell et al, 2008), but due to declining populations because of exploitation for both capture fisheries and capture-based aquaculture, E. bleekeri has been assessed as Near Threatened (Russell et al, 2008). In India, E. bleekeri is exploited along the western and eastern coasts using trawls and traditional fishing gears (Kandula et al, 2015;Mathew, 2003;Vargese et al, 2017), but no information is available on the magnitude of catches, status and dynamics of populations or other fishery-induced wffect. This data deficiency on the demography and fishery status of E. bleekeri in India, where a major fishery exists and throughout its range, poses a significant challenge to their effective management and hampers updated species assessments for the IUCN Red List.…”
mentioning
confidence: 99%